2019
DOI: 10.3354/esr01001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment of age-0 pallid sturgeon and shovelnose sturgeon: implications for surrogacy

Abstract: Validation is critical when considering potential surrogates for endangered species research. The pallid sturgeon Scaphirhynchus albus is federally endangered in the USA, whereas the congeneric shovelnose sturgeon S. platorynchus is common. Inadequate food availability during early life history is a hypothesized factor limiting recruitment of pallid sturgeon in the lower Missouri River, USA, and an established surrogate relationship with shovelnose sturgeon would dramatically expedite research efforts related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…These results are consistent with most of the previous diet studies conducted in mainstem habitats of the LMOR (Civiello et al, 2018;Gosch et al, 2016;, but additional work has suggested that age-0 sturgeon may be able to feed opportunistically depending on prey availability. For example, Gosch, Gemeinhardt, Civiello, Harrison, and Bonneau (2019) Interestingly, this study is the first published report from the LMOR documenting empty stomachs in large age-0 sturgeon (50-88 mm). This was unexpected because these individuals were captured on the floodplain and empty stomachs in the LMOR were previously restricted to small individuals ≤21 mm (Civiello et al, 2018;Gosch et al, 2016).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These results are consistent with most of the previous diet studies conducted in mainstem habitats of the LMOR (Civiello et al, 2018;Gosch et al, 2016;, but additional work has suggested that age-0 sturgeon may be able to feed opportunistically depending on prey availability. For example, Gosch, Gemeinhardt, Civiello, Harrison, and Bonneau (2019) Interestingly, this study is the first published report from the LMOR documenting empty stomachs in large age-0 sturgeon (50-88 mm). This was unexpected because these individuals were captured on the floodplain and empty stomachs in the LMOR were previously restricted to small individuals ≤21 mm (Civiello et al, 2018;Gosch et al, 2016).…”
Section: Discussionmentioning
confidence: 69%
“…Subsequently, shovelnose sturgeon recruitment appears to be occurring in the LMOR. For example, Steffensen, Stukel, and Shuman (2014) consume similar prey types (Gosch et al, 2018(Gosch et al, , 2019 in comparable amounts (Gosch et al, 2019)…”
Section: Discussionmentioning
confidence: 99%
“…The shovelnose sturgeon tends to be smaller in size and have a shorter lifespan than pallid sturgeon (Tranah, Campton, & May, 2004). Macroinvertebrates are important prey for both shovelnose sturgeon and pallid sturgeon, notably in early life stages (Gosch, Gemeinhardt, Civiello, Harrison, & Bonneau, 2019;Hay, Franti, Marx, Peters, & Hesse, 2008;Rapp, 2014;Sechler et al, 2012;Seibert, Phelps, Tripp, & Garvey, 2011;Wanner, Shuman, & Willis, 2006).…”
mentioning
confidence: 99%
“…Shovelnose sturgeon and pallid sturgeon survival and growth may be influenced by macroinvertebrate prey availability for larval sturgeon in the lower Missouri River and MMR (Gosch et al, 2016;Gosch et al, 2019;Jacobson et al, 2016). Previous studies have evaluated and accepted the use of shovelnose sturgeon as diet surrogates for pallid sturgeon (Braaten, Fuller, & McClenning, 2007;Sechler et al, 2012;Harrison, Slack, & Killgore, 2014;Civiello et al, 2018;Gemeinhardt et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation